Clinical study of cerebral palsy in 408 children with periventricular leukomalacia - SHANG, QING (Exp Ther Med, 2015)
This study aimed to investigate the high risk factors, cerebral palsy (CP) subtypes and comorbidities of periventricular leukomalacia (PVL). Based on treatment conditions at a specialist hospital, a cross-sectional clinical study and retrospective analysis of computed tomography and magnetic resonance imaging examinations was conducted to evaluate the risk factors, subtypes and comorbidities of CP in children with PVL. Among the 408 children with PVL, 8.58% were born with a weight of ≤1,500 g and 44.36% were born with a weight of ≥2,500 g. In addition, 36.76% of these children had a gestational age of ≤32 weeks and 37.75% had a gestational age of ≥37 weeks. The proportion of the children born with various high risk factors was 95.59%, including perinatal infections and hypoxia. Severe PVL was observed in preterm infants (63.41% with a gestational age of <28 weeks and 21.95% with a gestational age of 28–30 weeks) and low-birth weight infants, which were prone to quadriplegia (43.90%). The common comorbidities included visual and auditory disorders, epilepsy, mental retardation and language barriers. Visual and auditory disorders (26.96%) were the most common comorbidities. PVL was identified primarily in premature and low-birth weight infants. The degree of PVL was found to be negatively correlated with gestational age and birth weight. The degree of PVL in the full-term infants correlated with exposure to infections or hypoxia. Quadriplegia is common among the various subtypes of CP. Visual and hearing disorders are the most common comorbidities of CP; these comorbidities occurred most frequently with quadriplegia.